Enhancing financial literacy and economy in maritime management education: The role of case studies and simulations - Agung Kwartama (Research and Development in Education (RaDEn), 2025)
The growing complexity of the maritime industry underscores the importance of economic management as a critical competency for professionals navigating challenges in shipping, port operations, and sustainability. This study explores the integration of financial literacy and sustainability into maritime management education to align with industry demands. By focusing on practical tools such as case studies and simulations, the research provides a comprehensive analysis of how these methodologies enhance economic decision-making skills and operational efficiency. Through a qualitative approach, semi-structured interviews and open-ended questionnaires were conducted with 40 participants, including maritime professionals, educators, and graduates. Thematic analysis revealed that financial literacy equips students with a deeper understanding of economic principles, enabling informed decisions in resource allocation, risk management, and sustainability planning. Case studies and simulations emerged as transformative tools, fostering critical thinking and bridging the gap between theoretical learning and industry application. Despite these successes, the study also identifies areas for growth, particularly in embedding sustainability within financial decision-making frameworks. The findings emphasize the need for collaborative efforts between academia and industry to address pedagogical challenges, optimize resource utilization, and enhance curriculum relevance. This research contributes to advancing economic management education by highlighting actionable strategies to develop a workforce that is both financially literate and sustainability-focused, ensuring resilience in an evolving maritime sector.